Time Management sebagai Prediktor Happiness pada Kelompok Usia Dewasa Muda - Dania Aris Dyanti; Dewa Fajar Bintamur (Jurnal Ilmiah Psikologi MIND SET, 2018)
Young adults that have a high resolution and busy life to do, really need time management skills to help manage time effectively and reduce stress. Individual conditions that show the absence of stress is one component of the concept of happiness, so this study wants to find out whether time management is a predictor of happiness in young adults. Time management measurements were carried out using ATMS and measurement of happiness using OHQ. Data collection was carried out online on 320 participants. Regression analysis conducted shows that time management is a significant predictor for increasing happiness in young adults. The results of this study became the development of previous research related to the relationship between time management and happiness. regarding time management, individuals are better able to use now, allocating time to balance between working and carrying out other activities such as a form of comfort in life.